DeGen Artificial Intelligence: Challenges and Opportunities of AI Applications - Marsili, M. (European Cybersecurity Journal (ECJ), 2025)
Generative artificial intelligence (AI) is revolutionizing various fields, yet it also presents significant ethical, social, and technical challenges. This paper explores the dual nature of generative AI, highlighting its potential for innovation alongside its capacity for misuse, which we term “degenerate AI”. We will examine ethical dilemmas such as bias and misinformation, societal impacts including privacy and employment, and technical challenges related to system integrity and transparency. Additionally, we propose regulatory frameworks to ensure responsible AI development and deployment. This study aims to contribute to the discourse on AI ethics and governance, providing valuable insights for policymakers, technologists, and society.